precal

posted by .

sec^4x-tan^4x=1+2tan^2x

  • precal -

    sec^4 = (tan^2+1)^2 = tan^4 + 2tan^2 + 1
    subtract and voila.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Integration

    Intergrate ¡ì sec^3(x) dx could anybody please check this answer. are the steps correct?
  2. calculus

    find dy/dx y=ln (secx + tanx) Let u= secx + tan x dy/dx= 1/u * du/dx now, put the derivative of d secx/dx + dtanx/dx in. You may have some challenging algebra to simplify it. Use the chain rule. Let y(u) = ln u u(x) = sec x + tan x …
  3. Math - Trigonometry

    Verify the following: 1. cos x/(1-sinx)= sec x + tan x 2. (tanx+1)^2=sec^2x + 2tan x 3. csc x = )cot x + tan x)/sec x 4. sin2x - cot x = -cotxcos2x
  4. Trig.

    sec^2xcotx-cotx=tanx (1/cos)^2 times (1/tan)-(1/tan)=tan (1/cos^2) times (-2/tan)=tan (-2/cos^2tan)times tan=tan(tan) sq. root of (-2/cos^2)= sq. root of (tan^2) sq. root of (2i)/cos=tan I'm not sure if I did this right. If I didn't, …
  5. Calculus

    Evaluate the indefinite integral integral sec(t/2) dt= a)ln |sec t +tan t| +C b)ln |sec (t/2) +tan (t/2)| +C c)2tan^2 (t/2)+C d)2ln cos(t/2) +C e)2ln |sec (t/2)+tan (t/2)| +C
  6. trig

    prove: (tan x + sec x)^2 = 2sec^2 x + 2tan x sec x - 1
  7. trig

    prove: (tan x + sec x)^2 = 2sec^2 x + 2tan x sec x - 1
  8. calculus (check my work please)

    Not sure if it is right, I have check with the answer in the book and a few integral calculators but they seem to get a different answer ∫ sec^3(x)tan^3(x) dx ∫ sec^3(x)tan(x)(sec^2(x)-1) dx ∫ tan(x)sec(x)[sec^4(x)-sec^2(x)] …
  9. Trigonometry

    1.Solve tan^2x + tan x – 1 = 0 for the principal value(s) to two decimal places. 6.Prove that tan y cos^2 y + sin^2y/sin y = cos y + sin y 10.Prove that 1+tanθ/1-tanθ = sec^2θ+2tanθ/1-tan^2θ 17.Prove that …
  10. Trigonometry desperate help, clueless girl here

    2. solve cos 2x-3sin x cos 2x=0 for the principal values to two decimal places. 3. solve tan^2 + tan x-1= 0 for the principal values to two decimal places. 4. Prove that tan^2(x) -1 + cos^2(x) = tan^2(x) sin^2 (x). 5.Prove that tan(x) …

More Similar Questions